THE RELATIONSHIP EXCLUSIVE BREASTFEEDING WITH THE MENSTRUAL CYCLE IN BREASTFEEDING MOTHERS (Studies In Puskesmas Bungkal, District Bungkal, Ponorogo ) - Andika Willy; Sri Sayekti; Anin Wijayanti (STIKES Insan Cendekia Medika Jombang, 2011)
Many women experience problems due to the difficulty of exclusive breastfeeding breast milk out so that mothers choose to replace it with formula. Breastfeeding pattern is closely related to the return of fertility, which can be measured either by the return of the menstrual cycle after childbirth. The purpose of this study was to determine the relationship of exclusive breastfeeding with the menstrual cycle in breastfeeding mothers in Puskesmas Bungkal, District Bungkal, Ponorogo. The design of this analytic cross-sectional study. The study was conducted in March-July 2014, the entire population is lactating mothers with infants aged 6-7 months as many as 59 breastfeeding mothers with a total sampling technique sampling. Independent variables namely exclusive breastfeeding and menstrual cycle dependent variable.Measuring instrument using a questionnaire.Data processing using Editing, Coding, Tabulating.The statistical test using the chi square test. The results showed the majority of exclusive breastfeeding provides a non-exclusive breastfeeding 31 respondents (52.54%) and almost half the number of exclusively breastfed 28 respondents (47.46%). With the normal menstrual cycle a number of 37 respondents (62.71%) and an abnormal number of 22 respondents (37.29%). The results of chi square test with an error rate of α=0.05 was found that the ρ value = 0.000 <0.05, which means that H1 is accepted. The conclusion of this study is that there is a relationship of exclusive breastfeeding with the menstrual cycle in breastfeeding mothers in Puskesmas Bungkal, District Bungkal, Ponorogo. The results of this research can be used by midwives to provide KIE on exclusive breastfeeding in breastfeeding mothers to provide breast milk to their babies, especially in the Puskesmas Bungkal, District Bungkal, Ponorogo.